2014
DOI: 10.1128/mcb.00279-14
|View full text |Cite
|
Sign up to set email alerts
|

RORα Binds to E2F1 To Inhibit Cell Proliferation and Regulate Mammary Gland Branching Morphogenesis

Abstract: Retinoic acid receptor-related orphan nuclear receptor alpha (ROR␣) is a potent tumor suppressor that reduces cell proliferation and inhibits tumor growth. However, the molecular mechanism by which it inhibits cell proliferation remains unknown. We demonstrate a noncanonical nuclear receptor pathway in which ROR␣ binds to E2F1 to inhibit cell cycle progression. We showed that ROR␣ bound to the heptad repeat and marked box region of E2F1 and suppressed E2F1-regulated transcription in epithelial cells. Binding o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…286290 These antitumor effects of RORs have contributed to decreased cell proliferation as well as inhibition of the EMT. 286,289,291 The inverse correlation between RORα/γ expression and tumorigenesis suggests that agonists might inhibit tumor growth and progression and provide a promising new strategy for anticancer therapy.…”
Section: Melanoma Management: What Is New Under the Sun?mentioning
confidence: 99%
“…286290 These antitumor effects of RORs have contributed to decreased cell proliferation as well as inhibition of the EMT. 286,289,291 The inverse correlation between RORα/γ expression and tumorigenesis suggests that agonists might inhibit tumor growth and progression and provide a promising new strategy for anticancer therapy.…”
Section: Melanoma Management: What Is New Under the Sun?mentioning
confidence: 99%
“…NR1F1 may stimulate ER + /cell-growth via ERα binding/activation or aromatase induction [63]. Besides inhibiting growth, NR1F1 exerts anti-invasive actions in ER − /cells and tumors [6466]. In ER − /cells and xenografts, transcriptional Semaphorin-3F induction via a ROR-Response-Element contributes to NR1F1 anti-invasive and growth-inhibitory activities [64].…”
Section: Enigmatic-orphansmentioning
confidence: 99%
“…In ER − /cells and xenografts, transcriptional Semaphorin-3F induction via a ROR-Response-Element contributes to NR1F1 anti-invasive and growth-inhibitory activities [64]. In addition, NR1F1 binds E2F1-transcription-factor , inhibits E2F1 -acetylation and transcriptional activity, reducing ductal epithelial-cell proliferation [66]. No studies on NR1F2 in breast-cancer are available and the number of publications involving NR1F3 is limited [64, 67, 68].…”
Section: Enigmatic-orphansmentioning
confidence: 99%
“…Previous studies have shown that cyclin D promotes Rb phosphorylation by binding to cyclin-dependent kinases. Phosphorylation of Rb promotes Rb-E2F1 complex separation and E2F1 target gene transcription, which promotes cell cycle progression and cell proliferation[22, 23]. To test whether niacin increases the release of Rb-bound E2F1 by enhancing the phosphorylation of Rb, an IP assay was carried out.…”
Section: Resultsmentioning
confidence: 99%